2020
DOI: 10.1021/acs.jafc.0c00044
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen and SO2Consumption of Different Enological Tannins in Relationship to Their Chemical and Electrochemical Characteristics

Abstract: The oxidative behavior of five commercial enological tannins of different sources (tea, grape marc, grape seed, untoasted oak, and toasted oak) was investigated in model wine solutions in the presence or absence of SO 2 . Solutions of the tannins were also analyzed for total phenolics, methyl cellulose precipitable tannins, high-performance liquid chromatography, and linear sweep voltammetry. Tea and oak-derived tannin solutions were characterized by the highest oxygen consumption rates,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 48 publications
3
23
1
Order By: Relevance
“…Ellagitannins are obtained from oak and chestnut wood [ 6 ], while gallotannins are mainly from galla and tara nuts [ 7 ]. Tea tannins, well known for their beneficial bioactivities [ 8 ], were also tested in model wine solutions by Ugliano, Slaghenaufi, Picariello and Olivieri 2020 [ 9 ], who showed that they were capable of rapidly consuming oxygen, although this is associated with an increased decline in the SO 2 content.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ellagitannins are obtained from oak and chestnut wood [ 6 ], while gallotannins are mainly from galla and tara nuts [ 7 ]. Tea tannins, well known for their beneficial bioactivities [ 8 ], were also tested in model wine solutions by Ugliano, Slaghenaufi, Picariello and Olivieri 2020 [ 9 ], who showed that they were capable of rapidly consuming oxygen, although this is associated with an increased decline in the SO 2 content.…”
Section: Introductionmentioning
confidence: 99%
“…In regard to enological tannins, Ugliano, Slaghenaufi, Picariello and Olivieri [ 9 , 18 ] ascertained that different types of commercial tannins increase the oxygen consumption rate (OCR) and affect sulfur dioxide during an oxidative process in model wine solution. Moreover, Rinaldi and Moio [ 19 ] showed that the addition of different types of enological tannins affects the astringency and determines different astringency subqualities in Sangiovese wine.…”
Section: Introductionmentioning
confidence: 99%
“…Strong and highly significant correlations were found for both total phenolics and total tannins when total AUC of linear sweep votammograms was considered (Figure 2), with regression equations of y = 0.0002x − 183.58 for total phenolics and y = 0.0001x − 155.52 for total tannins respectively. Previous studies have indicated that AUC of either total raw voltammograms or subsections thereof are well correlated with wine values for total phenolics [20] as well as with total phenolics or total tannins values of commercial tannin powders [11,21]. Other studies have shown that the phenolic content of oak extracts is highly representative of their antioxidant capacity [17] as well as of their ability to consume oxygen during wine storage [7,11].…”
Section: Discussionmentioning
confidence: 99%
“…Chemical and electrochemical analyses. Total phenolic index (TPI) and methyl cellulose precipitable tannins (MCPT) were determined as previously described [11]. Briefly, at the end of the extraction period, OAs extracts were centrifuged, and TPI was determined spectrophotometrically using the Folin-Ciocalteau reagent, with results being expressed as mg/L eq.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation